Learning hindrances and self-regulated learning strategies reported by undergraduate students: identifying characteristics of resilient students. Issue 12 (2nd December 2018) - Ainscough, Louise; Stewart, Ellen; Colthorpe, Kay; Zimbardi, Kirsten
ABSTRACT: Students in higher education face a variety of learning hindrances while studying at university. These hindrances may negatively impact on learning by distracting from study, or may enhance learning by encouraging students to address challenges as they arise. In the current study students were asked to describe their learning hindrances at a single point early in semester, and to outline the strategies for overcoming these hindrances in future. Five hindrance clusters were determined and differences between student academic subgroups were identified. Hindrances associated with difficulties understanding were reported most frequently by improving students, who had demonstrated resilience by passing second year biomedical science courses after failing in first year. Improving students were also most likely to report learning strategies that promote understanding. These results suggest that early interventions to encourage students to critically evaluate their understanding may benefit struggling students.